Individuelle Daten zu Kurzarbeitenden: Datenvalidierung und erste Befunde - Christian Kagerl; Thomas Kruppe (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Kurzarbeit ist ein bewährtes Instrument zur Beschäftigungssicherung in Krisen, letztmals während der Corona-Pandemie, als die Nutzung im April 2020 mit bis zu sechs Millionen Personen einen nie dagewesenen Höhepunkt erreichte. Allerdings ist sehr wenig darüber bekannt, welche Personen wie lange und wie häufig Kurzarbeitergeld bezogen haben. Für den Zeitraum zwischen März 2020 und Dezember 2021 schließt der vorliegende Forschungsbericht diese Lücke und stützt sich dabei auf statistische Verfahren, um repräsentative Aussagen aus unvollständigen Daten zu ermöglichen. Insgesamt zeigt sich, dass gering qualifizierte und gering verdienende Personen in der Pandemie deutlich stärker von Kurzarbeit betroffen waren. Erstens war die Kurzarbeitendenquote dort höher. Zweitens hatten diese Personengruppen im Schnitt einen höheren kurzarbeitsbedingten Entgeltausfall. Als die Nutzung der Kurzarbeit im Frühjahr 2020 ihren Höhepunkt erreichte, bezogen insgesamt etwa 19 Prozent der sozialversicherungspflichtigen Beschäftigten Kurzarbeitergeld, mit einem durchschnittlichen Entgeltausfall von 50 Prozent. Die Quote der Kurzarbeitenden betrug bei Personen ohne Berufsabschluss 22 Prozent, bei Personen mit Hochschulabschluss lediglich 14 Prozent. Noch gravierender waren die Unterschiede zwischen Gering- und Besserverdienenden: Ein Drittel aller Vollzeitbeschäftigten mit weniger als 2.000 Euro Bruttoverdienst war im April 2020 in Kurzarbeit, aber nur 14 Prozent der Beschäftigten mit mehr als 4000 Euro. Gleichzeitig hatten Beschäftigte mit weniger als 2.000 Euro Bruttomonatsverdienst im Fall von Kurzarbeit im Durchschnitt einen Entgeltausfall, der mit durchschnittlich über 50 Prozent 20 bis 25 Prozentpunkte höher lag als bei jenen mit Arbeitsentgelten über 4.000 Euro. Ein weiteres Ergebnis der Analysen ist, dass der erneute starke Anstieg der Kurzarbeit zum Jahreswechsel 2020/2021 hauptsächlich auf Beschäftigte mit geringer beruflicher Bildung bzw. geringem Verdienst zurückzuführen ist. Zugleich hat sich die Betroffenheit unterschiedlicher Berufsgruppen im Verlauf der Krise verändert: Der Anteil der Kurzarbeitenden war im Frühjahr 2020 bei Produktionsberufen am höchsten. Danach lag er bei Dienstleistungsberufen höher. Insbesondere bei Berufen im Bereich der personenbezogenen Dienstleistungen war der erneute Anstieg der Kurzarbeit besonders ausgeprägt. Auch der mittlere Entgeltausfall durch Kurzarbeit war bei den Dienstleistungsberufen von Anfang an höher. Mit der Erschließung von individuellen Daten zur Kurzarbeit ergeben sich trotz der unvollständigen Datenlage weitere Analysepotenziale, z.B. im Hinblick auf Längsschnittanalysen. – – Short-time work has proven to be a good instrument for securing employment in crises, most recently during the coronavirus pandemic, when its use reached an unprecedented peak in April 2020 with up to six million people being in short-time work simultaneously. However, very little is known about which people receive how much short-time working allowance. Short-time work is initiated by establishments, but the establishments' notification is accompanied by an accounting sheet listing all employees (subject to social security contributions) who are in short-time work. During the pandemic, information on the individual receipts of short-time working allowances for the period from March 2020 to December 2021 was automatically extracted for the first time, using an automated optical character recognition procedure. We show that many characters could not be recognized by the program and are therefore missing. In addition, there are a range of implausible values. After cleaning the data, we validate the newly generated data by comparing it with establishment-level short-time work data and existing administrative employee data sets. This allows us to generate a foundation of high-quality short-time work data. We then use marginal distributions for the number of people in short-time work (taken from the statistics department of the Federal Employment Agency) to carry out a weighting procedure (namely, iterative proportional fitting). Specifically, for each month, the marginal distributions by gender, establishment size, economic sector and region as well as the total work loss are taken into account. Using the weighting allows to make representative statements, also with regard to previously unknown dimensions of short-time work, e.g. by level of education during the pandemic. We show that the weighting procedure works well in this case (e.g. it produces weight distributions without outliers) and has a high degree of flexibility. In addition, the weighting shows, for example, that employees from large establishments with 250 or more employees are underrepresented in the data on the individual utilization of short-time work benefits. This selection appears to be due to the fact that the text recognition procedure aborted the extraction of data from long notification lists after an unspecified number of pages. Using the new- data and the weighting procedure, we calculate a series of new descriptive results on the use of short-time work during the pandemic. We focus on two measures: The ratio of short-time workers to all employees within a group and the average wage loss of short-time workers within a group. The average wage loss describes the share of wages which is lost due to short-time work and which is partially reimbursed by the Federal Employment Agency. Overall, the results show that low-skilled and low-income workers were significantly more affected by short-time work. Firstly, the short-time work rate was higher in these groups and, secondly, they had a higher average wage loss when in short-time work. At the short-time work peak in spring 2020, around 19 percent of all employees subject to social security contributions were in short-time work, with an average wage loss of 50 percent. The rate of employees in short-time work was 22 percent for those without a vocational degree, but only 14 percent for those with a university degree. The differences based on gross monthly pay were even greater for full-time employees: A third of all full-time employees with gross wages of less than 2,000 Euro were in short-time work in April 2020, but only 14 percent of employees earning wages higher than 4,000 Euro. At the same time, employees with gross monthly wages of less than 2000 Euro had an average wage loss in the event of short-time work that was - at more then 50 percent on average - 20 to 25 percentage points higher than for those earning wages higher than 4000 Euro. Another result of the analysis is that the sharp increase in short-time work at the turn of the year 2020/2021 is mainly driven by employees with a low level of education and relatively low wages. Looking at occupational patterns, we show that the short-time work rate in spring 2020 was highest in production occupations. Thereafter, it was higher in service occupations, especially in personal services, where the resurgence of short-time work during the second lockdown was particularly pronounced. In the case of short-time work, the average loss of wages is however higher in service occupations across the entire period. In conclusion, we note that - despite the incompleteness of the data - the new individual data on short-time work offer further potential, e.g. with respect to longitudinal analyses.
Keywords: 330; Kurzarbeit; Corona-Pandemie; Krisen